Multi-competency development: strategy to strengthen the resilience of human capital from unpredictable global disruption - Ratu Agung Bagus Ngurah Putra; Ni Made Ernawati; Ni Gst Nym Suci Murni; Putu Tika Virginiya (International Journal of Applied Sciences in Tourism and Events, 2023)
This research was conducted with the aim of building a new competency development strategy for workers so that they have multi-competence capabilities in an effort to survive in a situation of uncertainty. The object of this research is the four Wyndham hotel chains in Bali, Indonesia where an in-depth exploration is carried out on the Human Capital Aspect which includes Threshold Characteristics and Differentiation. Threshold Characteristics are essential characteristics consisting of Knowledge and Skills, while Differentiation characteristics which are superior distinguishing aspects consist of Self-Concept, Motives, and Treats. Using a mixed method research with an exploratory sequential approach, the researchers carried out three stages of research from qualitative research, and quantitative research to validating research results through Focus Group Discussions with policymakers from the four Wyndham hotel chains in Bali involved. Through all the stages of the research, the researchers developed a model of Multi-Competency Development, that is in accordance with the characteristics of Wyndham hotel employees. The model, which is named the Sundae Multi-Competency Development, consists of 6 steps including (1) Identification of Competency Trends; (2) Competency Recommendations; (3) Internal Intent Analysis; (4) Training and Development; (5) Certification; and (7) Own Multi-Competency. The research results in the recommendation of relevant new competencies to be developed in the Wyndham hotel chain in Bali, including Teaching, Marketing, and Cooking competencies.